Comparing mortality risk reduction, life expectancy gains, and probability of achieving full life span, as alternatives for presenting CVD mortality risk reduction: a discrete choice study of framing risk and health behaviour change - Grisolía, José M.; Longo, Alberto; Hutchinson, George; Kee, Frank (Elsevier, 2018)
The growing rate of obesity has recently required governments to divert considerable resources in the promotion of healthy lifestyles. We explored the relative effectiveness in inducing healthy behaviour change of three different communication strategies about the benefits of an intervention that reduces the mortality risks of cardiovascular disease (CVD) and encourages respondents to embrace healthier lifestyles. We designed a Discrete Choice Experiments questionnaire to analyse the trade-off between lifestyles, defined in terms of diet and exercise, and reduction in cardiovascular disease (CVD) mortality risk. We set three ways of framing an identical benefit: (A) as a reduction in mortality risk from cardiovascular disease, (B) as an increase in months of life expectancy, and (C) as an increase in the probability of reaching an individual's full lifespan. The experiment was tailored for each subject in the sample according to his/her individual's baseline information on diet and physical activity. During the period February 2010–July 2011, we interviewed 1008 individuals in Northern Ireland, split randomly into three samples for the three CVD risk reduction frames. Considering the models' goodness of fit and significance, we conclude that the most effective way of communicating these CVD health benefits is using an increase in life expectancy, since with this frame individuals are more inclined to state that they would change to a healthier lifestyle.